A Swift Guide to Butterflies of Mexico and Central America : Second Edition - Glassberg, Jeffrey (Book collections on Project MUSE., 2017)
A groundbreaking photographic field guide to almost all of Mexico's butterfly species and many of Central America'sThis is a revised second edition of a groundbreaking photographic field guide to the butterflies of Mexico and Central America. Written by Jeffrey Glassberg, the pioneering authority on the field identification of butterflies, the guide covers more than 2,000 species and features over 3,700 large, gorgeous color photographs, the very best images available, accompanied by authoritative facing-page text. This second edition includes more species, more than 1,500 new photos, and updated text, maps, and species names. And range maps, field marks, and host plants are included for all Mexican butterflies. The result is an ideal field guide that will enable you to identify almost every butterfly you see. A revised second edition of a groundbreaking guide, featuring more species, more than 1,500 new photos, and updated text, maps, and species namesThe first complete guide to Mexican butterfliesCovers almost all of Mexico's more than 1,700 species, plus many Central American species, including more than two-thirds of those in Costa RicaWritten by the pioneering authority on the field identification of butterfliesBeautifully illustrated with more than 3,700 color photographs that highlight key identification featuresRange maps, field marks, and host plants for all Mexican speciesAuthoritative facing-page textAn invaluable tool for field identification.